Male IDUs who have sex with men in England, Wales and Northern Ireland: are they at greater risk of bloodborne virus infection and harm than those who only have sex with women?. Issue 6 (23rd May 2012) - Marongiu, Andrea; Hope, Vivian D; Parry, John V; Ncube, Fortune
Abstract : Objectives: In the UK, although transmission of HIV among injecting drug user (IDUs) has been limited since the 1980s, IDUs and men who have sex with men (MSM) have higher HIV and hepatitis C virus (HCV) prevalences than the general population. MSM who are also IDUs (MSM-IDUs) may therefore have a higher risk of infection than male IDUs who only have sex with women. Methods: Analysis of data from a national survey of IDUs attending services (England, Wales and Northern Ireland) between 1998 and 2007, which collected demographic and behavioural data and oral fluid samples for HIV and HCV antibody testing. Results: Of the 8671 men who reported injecting drugs and having sex during the preceding year, 96% (8354) were men who only had sex with women (MSW). MSM-IDUs and MSW-IDUs had similar age and number of years of injecting. MSM-IDUs had a higher prevalence of HIV (adjusted OR=4.08, 95% CI 1.9 to 8.5) and of HCV (adjusted OR =1.34, 95% CI 1.1 to 1.8) and were about four times (adjusted OR =3.78, 95% CI 2.9 to 4.9) more likely to have unprotected sex with multiple partners. Among those who injected in the 4 weeks prior to participation, the MSM-IDUs had a higher level of needle/syringe sharing (adjusted OR =1.72, 95% CI 1.3 to 2.2). Discussion: MSM-IDUs have a fourfold higher risk of HIV; HCV prevalence in MSM-IDUs is a third higher than among MSW-IDUs, suggesting elevated risk from injecting and possibly sexual transmission. These findings emphasise the need for public health interventions specifically targeted at MSM-IDUs.